Analisis Faktor yang Mempengaruhi Mahasiswa dalam Memilih Sekolah Tinggi Manajemen Informatika dan Komputer (STIMIK) di Kota Semarang - Heru Yulianto (Jurnal Ilmiah Aset, 2008)
In the globalization era, competition need qualified human resources who has competitive advantage, to prepare qualified human resources need qualified education. In the growth of information management and computer, needs human who can handle this technology, so the information management and computer college can answer this challenge. The student who want to study in this college was rapidly growth, so this research focus in factor analysis considered by student to choose information management and computer. This research use 3 information management and computer college in Semarang, with 200 respondent choosed as sample use purposive sample method and data collected, price, location, culture, social class, family reference group, personal traits, process, physical condition, perception, study and attitude. This research test use factor analysis. This research results point to 15 factors and 37 variables with varimax factor rotations times, choose the 11 factor and 31 variable withmanagement and computer college must improve the service mechanism, service quality, qualified college leader, computer equipment to improve the studying activity.